Karakteristik Bangunan â€œBale Metenâ€ Serta Proses Pembangunannya - Desak Made Sukma Widiyani; Frysa Wiriantari (Program Studi Arsitektur, Fakultas Teknik Universitas Warmadewa, 2019)
Traditional Balinese architecture is very closely related to culture and religion of Hindu in Bali. Traditional Balinese architecture is also inseparable from the philosophies or concepts contained. The Balinese architecture can be divided into several types of buildings, namely, buildings of Pura (holy places) and buildings of Puri (houses/housing). Traditional Balinese housing consists of several buildings that have different functions, building form, and layouts. Buildings in traditional Balinese housing are, bale meten/bale daja, bale dangin/bale adat, bale dauh, paon/kitchen, jineng/klumpu, and merajan/sanggah (holy place). Bale Daja/Bale Meten is the first building built in traditional Balinese housing. The study of the characteristics of bale meten was carried out with the aim of knowing the characteristics and development process of bale meten sakutus buildings in terms of layout in a housing area, building functions, building form, and materials used. The results of this study will also add references about bale meten especially bale meten sakutus so that it can preserve the values contained. The research approach used in this study is based on descriptive qualitative research methods with a naturalistic approach. This research method is used to describe the facts that occur in the field related to the condition of bale meten in the case study, the functions of buildings, building form, layout and the development process. This study uses three case studies of bale meten sakutus in the Gianyar and Badung regions. This is due to the lack of the existence of bale meten sakutus buildings in other areas.